A learning health system approach to COVID‐19 exposure notification system rollout - Ming Tai‐Seale; Nicole May; Amy Sitapati; Christopher A. Longhurst (Wiley, 2022)
Abstract Introduction Digital exposure notification (EN) approaches may offer considerable advantages over traditional contact tracing in speed, scale, efficacy, and confidentiality in pandemic control. We applied the science of learning health systems to test the effect of framing and digital means, email vs Short Message Service (SMS), on EN adoption among patients of an academic health center. Methods We tested three communication approaches of the Apple and Google EN system in a rapid learning cycle involving 15 000 patients pseudorandomly assigned to three groups. The patients in the first group received a 284‐word email that presented EN as a tool that can help slow the spread. The patients in the second group received a 32‐word SMS that described EN as a new tool to help slow the spread (SlowTheSpreadSMS). Patients in the third group received a 47‐word SMS that depicted the system as a new digital tool that can empower them to protect their family and friends (EmpowerSMS). A brief four‐question anonymous survey of adoption was included in a reminder message sent 2 days after the initial outreach. Results One hundred and sixty people responded to the survey within 1 week: 2.33% from EmpowerSMS, 0.97% from SlowTheSpreadSMS, and 0.53% from emails; 29 (41.43%), 24 (41.38%), and 11 (34.38%) reported having adopted EN from each group, respectively. Patient reported barriers to adoption included iOS version incompatibility, privacy concerns, and low trust of government agencies or companies like Apple and Google. Patients recommended that healthcare systems play an active role in disseminating information about this tool. Patients also recommended advertising on social media and providing reassurance about privacy. Conclusions The EmpowerSMS resulted in relatively more survey responses. Both SMS groups had slightly higher, but not statistically significant EN adoption rates compared to email. Findings from the pilot not only informed operational decision‐making in our health system but also contributed to EN rollout planning in our State.